2018
DOI: 10.1016/j.bone.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Dampening of the bone formation response following repeat dosing with sclerostin antibody in mice is associated with up-regulation of Wnt antagonists

Abstract: Administration of antibodies to sclerostin (Scl-Ab) has been shown to increase bone mass, bone mineral density (BMD) and bone strength by increasing bone formation and decreasing bone resorption in both animal studies and human clinical trials. In these studies, the magnitude and rate of increase in bone formation markers is attenuated upon repeat dosing with Scl-Ab despite a continuous and progressive increase in BMD. Here, we investigated whether the attenuation in the bone formation response following repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 40 publications
3
26
1
Order By: Relevance
“…(39,53,(58)(59)(60) It has been proposed that the dampening effects following long-term SclAb treatment may be caused by a large and acute upregulation in inhibitory regulators of bone formation (SOST, DKK1). (38) We observed a similar upregulation of SOST and DKK1 with SclAb treatment. This compensatory response has been documented in the acute phase of treatment with significant upregulation observed following a single dose of SclAb.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…(39,53,(58)(59)(60) It has been proposed that the dampening effects following long-term SclAb treatment may be caused by a large and acute upregulation in inhibitory regulators of bone formation (SOST, DKK1). (38) We observed a similar upregulation of SOST and DKK1 with SclAb treatment. This compensatory response has been documented in the acute phase of treatment with significant upregulation observed following a single dose of SclAb.…”
Section: Discussionsupporting
confidence: 66%
“…The panel represents a subset of markers in the bone remodeling cycle-many of which have been identified as key targets for SclAb therapy in prior animal studies. (38)(39)(40)44) Because of the rarity of the OI bone tissue and the size of the available harvested bone (which affected the amount of total nucleic acid we were able to extract), we chose to analyze only one housekeeping gene (HPRT1), which has been documented in the literature as a stable gene across experimental conditions in human bone studies. (45,46) Pooled, purified RNA samples underwent reverse transcription using qScript cDNA SuperMix (Quanta Biosciences, Gaithersburg, MD, USA) using 1.5 μg of retro-transcribed RNA per reaction followed by thermocycling (C1000 Thermal Cycler; Bio-Rad Laboratories, Hercules, CA, USA) according to the manufacturer's recommendations.…”
Section: Taqman Qpcr Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The role of other secreted inhibitors in the compensatory expression mechanism are unknown. Canonical WNT signaling antagonists such as WISE (65), sFRP4 (66), and NOTUM (67), are associated with skeletal phenotypes in mice when mutated either globally or selectively in bone cells, and sclerostin inhibition enhances a number of these transcripts in mouse bone (68). Whether pharmacologic modulation of these or other members of the secreted WNT inhibitory milieu can improve or otherwise tailor the efficacy of sclerostin and/or Dkk1 neutralizing therapy is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Scl-Ab administration down-regulated both WIF1 and SFRP2 expression in estrogen-treated cells, however it appeared to have no signi cant in uence on estrogen de cient cells. This may be a result of our experimental timelines, in which we analysed WNT antagonist expression after only 2 days of Scl-Ab treatment, whereas an in vivo study showed an upregulation in Wnt antagonist expression after 1 week of Scl-Ab administration [64].…”
Section: Discussionmentioning
confidence: 99%